2016
DOI: 10.3758/s13421-016-0593-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent perceptual grouping effects in the evaluation of simple arithmetic expressions

Abstract: Landy and Goldstone (2007a demonstrated that an explicit rule, operator precedence for simple arithmetic expressions, is enforced in part by perceptual processes like unit formation and attention. When perceptual grouping competes with operator precedence, errors increase. We replicated this result (Exp. 1) and investigated whether perceptual grouping effects persist when the visual stimulus is presented briefly and then masked (Exp. 2) and when verbal recoding is encouraged through vocal expression (Exp. 3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…They found that operands are more likely to be summed when they are widely spaced, and more likely to be multiplied when the operands are narrowly spaced ( Landy and Goldstone, 2010 ). Consistently, Rivera and Garrigan (2016) replicated the study of Landy and Goldstone (2010) recently and confirmed that the physical spacing of formal equations has a large impact on successful evaluations of the expressions ( Rivera and Garrigan, 2016 ). Katz and Knops (2014) were the first to explore the operational momentum effect in multiplication and division.…”
Section: Introductionsupporting
confidence: 70%
“…They found that operands are more likely to be summed when they are widely spaced, and more likely to be multiplied when the operands are narrowly spaced ( Landy and Goldstone, 2010 ). Consistently, Rivera and Garrigan (2016) replicated the study of Landy and Goldstone (2010) recently and confirmed that the physical spacing of formal equations has a large impact on successful evaluations of the expressions ( Rivera and Garrigan, 2016 ). Katz and Knops (2014) were the first to explore the operational momentum effect in multiplication and division.…”
Section: Introductionsupporting
confidence: 70%
“…Other research indicates that people are heavily influenced by groupings based on perceptual properties when performing not only algebra but simple arithmetic as well. The influence of spacing persists even when the mathematical notation is only presented briefly and then masked and when verbal encoding is encouraged (Rivera & Garrigan, 2016), and these perceptual effects combine with traditional order-of-operations rules in compound expressions ( Jiang, Cooper, & Alibali, 2014). Effective training procedures for teaching math and science often deemphasize explicit, verbalizeable knowledge, instead focusing on perceptual skill learning through adaptive training (Kellman, Massey, & Son, 2010;Mettler & Kellman, 2014).…”
Section: Employing Visual Grouping Routines For Algebramentioning
confidence: 99%
“…And, indeed, people are sensitive to these visuospatial norms. When they judge the validity of an algebraic equation, performance is systematically worse if visual grouping or proximity conflicts with operator precedence (e.g., less space around addition than around multiplication), and systematically improved if visuospatial features align with operator precedence (Landy & Goldstone, 2007a; Rivera & Garrigan, 2016). Conversely, when adults write out algebraic expressions, they place terms connected by a higher-precedence operation (e.g., multiplication) closer together than those connected by a lower-precedence operation (e.g., addition; Landy & Goldstone, 2007b).…”
Section: Introductionmentioning
confidence: 99%